Trends and patterns in EU(7)-PIM prescribing to elderly patients in Germany - Selke Krulichová, Iva; Selke, Gisbert W; Thürmann, Petra A (European journal of clinical pharmacology, 2021)
PURPOSE: The aim of this study was to explore patterns and long-term development in prescribing potentially inappropriate medication (PIM) according to the EU(7)-PIM list to elderly patients in Germany. METHODS: We analysed anonymized German claims data. The study population comprised 6.0 million insured individuals at least 65 years old, including all their prescriptions reimbursed in 2019. For the analysis of long-term development, we used data for the years 2009-2019. Factors associated with PIM prescribing were considered from two perspectives: patient-oriented analysis was performed with logistic regression and prescriber-oriented analysis was performed with multiple linear regression. RESULTS: EU(7)-PIM prevalence was reduced from 56.9% in 2009 to 45.1% in 2019. Average annual volume (DDDs/insured) decreased from 145 in 2009 to 121 in 2019. These figures are substantially greater than those for the older PRISCUS list. The majority of investigated ATC level 2 groups with the highest EU(7)-PIM DDD volume exhibited substantial decreases; moderate increases were found for antihypertensive and urological drugs. Antithrombotics increased strongly with the introduction of direct oral anticoagulants. The most prevalent EU(7)-PIM medication was diclofenac; however, in the age group 85+ years, apixaban was twice as prevalent as diclofenac. Polypharmacy, female sex, age < 90 years, need for nursing care and living in Eastern regions were identified as risk factors. Prescriber specialty was the most marked factor in the prescriber-oriented analysis. CONCLUSION: Although the use of EU(7)-PIMs has been declining, regional differences indicate considerable room for improvement. The comparison with PRISCUS highlights the necessity of regular updates of PIM lists.
Keywords: Sex Factors; PRISCUS list; polypharmacy; Humans; Potentially inappropriate medication; seznam potenciálně nevhodných léčiv; Claims data; Potentially Inappropriate Medication List; Aged; Residence Characteristics; Elderly; věkové faktory; pojistná škoda - přezkoumání; Insurance Claim Review; senioři; lidé; Polypharmacy; Germany; Německo; sexuální faktory; charakteristiky bydlení; Retrospective Studies; EU(7)-PIM list; Aged, 80 and over; Cross-Sectional Studies; senioři nad 80 let; retrospektivní studie; Age Factors; průřezové studie